2014
DOI: 10.3233/wor-131778
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, incidence and persistence of symptoms from the eyes among professional computer users

Abstract: BACKGROUND: Symptoms from the eyes are common among computer users. Knowledge is scarce about these problems, however. OBJECTIVES:The aim was to study risk-factors, incidence and persistence of eye-symptoms among professionally active computer users. METHODS: This was a questionnaire based prospective study where 1283 males and females from different professions and companies answered a baseline questionnaire about individual factors and working conditions, e.g. duration of daily computer work, comfort of scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 64 publications
4
40
0
Order By: Relevance
“…The higher prevalence of CVS in females observed in our study (85.1% women vs. 66.1% men) is also consistent with numerous previous reports [13,[48][49][50][51][52]. This association with sex could be related to dry eye [53][54][55][56].…”
Section: Discussionsupporting
confidence: 93%
“…The higher prevalence of CVS in females observed in our study (85.1% women vs. 66.1% men) is also consistent with numerous previous reports [13,[48][49][50][51][52]. This association with sex could be related to dry eye [53][54][55][56].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies, we found that the prevalence of asthenopia was higher in females than in males (56.4% versus 50.4% p < 0.001) (Toomingas et al. ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the interblink interval during cognitive demanding VDU work is lower and with an increase in incomplete blinks, which may be associated with visual fatigue . In general, extended VDU work is associated with DE symptoms, the more the more cognitive demanding tasks . For draft, humidity, temperature, environmental exposures, and psychological factors, see above.…”
Section: Resultsmentioning
confidence: 99%
“…Frequent short breaks (0.5–1 minute) should be encouraged to minimize DE symptoms and at the same time maintain or even improve work productivity …”
Section: Resultsmentioning
confidence: 99%